Data aggregation in wireless sensor network for optimizing network lifetime - Qifen DONG; Hongyu CHEN; Guojun LI; Kang WANG; Zhen HONG (Dianxin kexue)
Taking target tracking in wireless sensor network（WSN）as application background，data aggregation for optimizing network lifetime based on extended Kalman filter method was researched，and an algorithm which considered both tracking accuracy and node energy to real-time schedule node groups involved in the data integration was designed.Simulations show that the proposed algorithm makes the tracking results do not deviate from the trajectory of target as long as the target speed is within a certain speed range.In addition，compared with the Random method and the All method，the proposed algorithm greatly prolongs network lifetime.